Fronto-striatal effective connectivity of working memory in adults with cannabis use disorder. (30th August 2018) - Ma, Liangsuo; Steinberg, Joel L.; Bjork, James M.; Keyser-Marcus, Lori; Vassileva, Jasmin; Zhu, Min; Ganapathy, Venkatesh; Wang, Qin; Boone, Edward L.; Ferré, Sergi; Bickel, Warren K.; Gerard Moeller, F.
Highlights: This study investigated working memory in cannabis use disorder. Dynamic causal modeling was used to assess underlying neural circuits. Decreased right DLPFC to left caudate effective connectivity was found during higher memory demand. Increased effective connectivities from other prefrontal cortices to caudate were observed. May reflect negative effects of cannabis use and compensatory mechanism, respectively. Abstract: Previous working memory (WM) studies found that relative to controls, subjects with cannabis use disorder (CUD) showed greater brain activation in some regions (e.g., left [L] and right [R] ventrolateral prefrontal cortex [VLPFC], and L dorsolateral prefrontal cortex [L-DLPFC]), and lower activation in other regions (e.g., R-DLPFC). In this study, effective connectivity (EC) analysis was applied to functional magnetic resonance imaging data acquired from 23 CUD subjects and 23 controls (two groups matched for sociodemographic factors and substance use history) while performing an n -back WM task with interleaved 2-back and 0-back periods. A 2-back minus 0-back modulator was defined to measure the modulatory changes of EC corresponding to the 2-back relative to 0-back conditions. Compared to the controls, the CUD group showed smaller modulatory change in the R-DLPFC to L-caudate pathway, and greater modulatory changes in L-DLPFC to L-caudate, R-DLPFC to R-caudate, and R-VLPFC to L-caudate pathways. Based on previous fMRI studies consistently suggesting that greater brain activations are related to a compensatory mechanism for cannabis neural effects (less regional brain activations), the smaller modulatory change in the R-DLPFC to L-caudate EC may be compensated by the larger modulatory changes in the other prefrontal-striatal ECs in the CUD individuals.